Babad Bakalan Sebuah Data Baru Bagi Sejarah Indonesia Kuno - nfn. Masyhudi (Berkala Arkeologi, 1994)
Stories about saints are generally found in various historiographical texts or constitute local history. However, the correctness of the text is still questionable. Babad Bakalan is a text that as a whole reveals matters of a historiographical or local history, and the manuscript is reliable. On this occasion, a paper will be presented based on new data obtained in research on the Islamic Mataram Settlement and Transportation Route in Wonogiri Regency.